UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KESADARAN BERIBADAH SISWA - Ahmad Fahmi Alfian; M Mujiburrahman; S Sukari (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
This study aims to determine the efforts of Islamic Religious Education teachers in increasing students ' worship awareness. This study is a qualitativeresearch with research subjects 1st grade students PKTQ, teacher PAI, head unit pktq and curriculum section PKTQ in MIN 2 Sukoharjo. Data were taken using interviews, observation and documentation. While data analysis by means of data reductioni, data display and data verification. The result of this research is the efforts of Pai teachers in increasing awareness of student worship that is by direct interaction with students, giving good examples, inviting and practicing in goodness, giving gifts and giving punishment. Then the supporting factors in the process of increasing awareness of student worship is the support of parents, adequate community environment and supportive school environment. While the inhibiting factors are the lack of awareness of the students, lack of support from parents and poor student association.